Format Pertunjukan Cerita Wayang untuk Dalang Anak - Junaidi Junaidi (PANGGUNG, 2011)
Writing an article titled "The Story Puppet Show Format to Dalang Children"aims to offer a special puppet play structure concept to mastermind the child, in order to serve as the medium of continuity and development of puppet art for future generations. So far, the play is shown by the mastermind of children still using the packaging story to mastermind an adult or older, so there are some things that can not be understood and displayed in both the masterminds of the child, because the demands of philosophy and technique-oriented adult size. The foundation of the theory used is the structure of puppet plays and psychological developments of children, while the descriptive analytical method used. The result of such thinking plays puppet concept pertujukan format that can be used as a reference puppeteer for children.Keywords: format, stories, puppets, and the mastermind of children.